2012
DOI: 10.1177/0734904112462976
|View full text |Cite
|
Sign up to set email alerts
|

Development of polyureas with improved fire resistance

Abstract: The demand for improved damage control materials to address high strain rate impact has led to exploration of polyureas in this role. Polyureas show potential for retrofitting pre-existing platforms because they can be applied as a spray and have extremely fast cure times and low volatile organic compounds. However, they have been limited in use in enclosed spaces because of their flammability. In this article, synthetic and additive routes to improve polyurea flame retardancy are systematically explored. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…APP alone decreases the thermal stability of PU as consequence of the formation of phosphoric acid, which can act as a catalyst for PU degradation. 13 However, the other OP combinations did not improve the thermal stability. Poor thermal stability is observed in EG and A-78 combination, which may be attributed to the lower thermal stability of both additives.…”
Section: Effect Of Binary Mixture Of Conventional Frsmentioning
confidence: 95%
See 1 more Smart Citation
“…APP alone decreases the thermal stability of PU as consequence of the formation of phosphoric acid, which can act as a catalyst for PU degradation. 13 However, the other OP combinations did not improve the thermal stability. Poor thermal stability is observed in EG and A-78 combination, which may be attributed to the lower thermal stability of both additives.…”
Section: Effect Of Binary Mixture Of Conventional Frsmentioning
confidence: 95%
“…Sulfur compounds are also used in polycarbonate. [10][11][12] Recently, Underhill et al 13 have reported the fire resistance of PU using three different routes, chemical modification, additives, and surface coating. In earlier work from this laboratory, the effect of almost 50 individual FRs, from every class of conventional FRs, was used to evaluate the flammability of PU; the most efficacious materials were expandable graphite (EG), ammonium polyphosphate (APP), aluminum diethylphosphinate (OP 1314), and melamine polyphosphate (MPP), evaluated based on the percentage reduction of the peak heat release rate (HRR) from cone calorimetry at a heat flux of 50 kW/m 2 .…”
mentioning
confidence: 99%
“…Meanwhile, phosphorus-containing monomers can be used to synthesize phosphorus-containing PUreas with improved flame-retarding properties. 12 Diisocyanates are currently prepared from extremely toxic phosgene. Diisocyanates also show high toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…PUUs are currently prepared from diisocyanates and polyols with diamines as chain extenders. PUreas are prepared from diisocyanates and polyamines and are usually used as two-component systems in the protective coating/lining industry. PUUs and PUreas normally exhibit better mechanical properties than common PUs because urea groups provide additional hydrogen bonds. Meanwhile, phosphorus-containing monomers can be used to synthesize phosphorus-containing PUreas with improved flame-retarding properties . Diisocyanates are currently prepared from extremely toxic phosgene.…”
Section: Introductionmentioning
confidence: 99%